The Economists' Voice (De Gruyter, 2004)
The Economists' Voice creates a forum for readable analysis by leading economists on vital economic policy issues of our day. The focus is on the clear verbal presentation of important evidence-based arguments for a broad readership. Empirical papers on policy-relevant issues are also welcome.